Evaluation of drinking water quality in Xinjiang based on the improved comprehensive water quality index - Jie Li; Lingshuang Lv; Wei Zhe; Xixi Deng; Qin Lin; Rongxiang Xia; Ruonan Fu (Heliyon)
Objective: To evaluate the drinking water quality in cities and towns in Xinjiang. Methods: The testing data of 6543 water samples from the dry season and the wet season in 2023 were selected, and the drinking water quality in Xinjiang was evaluated and analyzed by using the Nemerow pollution index, the worst factor discriminant method and the weighted average method to calculate the comprehensive water quality index. Results: The comprehensive index of drinking water quality in Xinjiang was 0.36 ± 0.39, and the quality rate was 98.58 %. The water quality in the wet season (0.28 ± 0.45) was better than that in the dry season (0.44 ± 0.28), and water quality in the urban area (0.34 ± 0.20) was better than that in the rural area (0.37 ± 0.28). The water quality of conventionally treated water (0.35 ± 0.30) and other treatments (0.36 ± 0.21) was better than that of nontreated water (0.42 ± 0.84), and the water quality of the disinfected water (0.35 ± 0.29) was better than that of the nondisinfected water (0.39 ± 0.54). The water quality of deep wells (0.35 ± 0.25), rivers (0.35 ± 0.37), springs (0.35 ± 0.21), reservoirs (0.37 ± 0.28), others (0.37 ± 0.24), and shallow wells (0.37 ± 0.31) was significantly better than that of streams (0.90 ± 2.40) (P<0.05). Conclusion: The drinking water quality in Xinjiang is generally good, and the water can be safely drunk. Drinking water quality is mainly affected by the water period, sampling type, water source classification, and water supply method. Lakes, deep wells and rivers are the ideal drinking water sources in Xinjiang.